Full-biomass transparent liquid mulching film with photo-thermal conversion performance as well as preparation method and application of full-biomass transparent liquid mulching film
Through the fully biomass transparent liquid mulch, the photothermal conversion performance of nanocellulose is used to solve the problems of insufficient soil temperature in high altitude areas and environmental pollution of traditional mulch films, and more efficient agricultural production and environmental protection performance are achieved.
Patent Information
- Application Number
- CN202411876402.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-07
AI Technical Summary
Due to the thin atmosphere in high-altitude areas and high UV irradiation intensity, traditional polyethylene mulching film cannot effectively use strong UV rays to increase soil temperature, affecting crop growth and limiting yield. At the same time, traditional mulching film is not degradable, resulting in environmental pollution.
A fully biomass transparent liquid mulch is used to prepare nanocellulose containing lignin nanocellulose, biomass crosslinking agent, biomass plasticizer and gelatin. Nanocellulose is prepared by pretreatment of eutectic solvents to form a liquid mulch with photothermal conversion properties.
The mulch can effectively convert ultraviolet light into heat energy, increase soil temperature, improve crop growth environment, and at the same time reduce water vapor transmission, reduce ultraviolet ray damage to crops, reduce dependence on petrochemical raw materials, and achieve environmentally friendly and sustainable agricultural production.
Smart Images

Figure CN119570269A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of mulch films in agricultural production, and in particular to a full-biomass transparent liquid mulch film with photothermal conversion performance, and a preparation method and application thereof. Background Art
[0002] Due to the thin atmosphere in high altitude areas, the intensity of ultraviolet radiation is significantly higher than that in low altitude areas. This strong ultraviolet radiation poses a dual challenge to the growth environment of crops: on the one hand, this strong ultraviolet radiation not only affects the growth and development of crops, but also damages the leaves and stems of crops; on the other hand, despite the high intensity of ultraviolet radiation, the application effect of traditional mulch is limited due to the low temperature, especially in an environment with a large temperature difference between day and night. Traditional polyethylene mulch cannot effectively use strong ultraviolet rays to increase soil temperature, affecting crop growth and limiting its yield.
[0003] At the same time, the use of traditional polyethylene mulch films also brings about environmental pollution problems, especially "white pollution". Due to its non-degradability, if the film is not recycled properly, it will remain in the soil for a long time, destroying the soil structure, causing soil compaction, and seriously affecting agricultural production and the ecological environment. In the face of increasingly prominent environmental problems, a new type of degradable and environmentally friendly mulch film is urgently needed to replace traditional mulch films.
[0004] Although there are some research and development and applications of biomass mulch in the market, the existing related patents can hardly achieve the configuration of all biomass components. Many so-called "biomass mulch" still rely on some synthetic materials to enhance their mechanical strength or durability, and fail to completely get rid of the impact of traditional materials on the environment. This not only limits the improvement of its environmental performance, but also weakens its degradation efficiency to a certain extent. Therefore, the development of a transparent liquid mulch that can truly achieve full biomass configuration and has photothermal conversion performance is of great significance to promoting the sustainable development of agriculture.
[0005] At present, there are patents that disclose related technologies. For details, see Chinese patent CN117048163A, which discloses a biodegradable warming ground film, which is a double-layer film structure, including a first film and a second film, and the first film is a blue biodegradable film, and the second film is a black biodegradable film. Chinese CN117946507A discloses a method for preparing a biodegradable weed-killing and warming ground film, which belongs to the field of polymer compositions. The preparation method includes preparing carbon black micropowder loaded with herbicides, preparing carbon black micropowder cellulose composites, fatty amine treatment, granulation, and blow molding. This technical solution achieves a warming effect through a black film and a carbon black micropowder composite, but its main disadvantage is that it limits the transmittance of light, thereby affecting the light requirements of crops to a certain extent. Especially in high-altitude areas, due to the higher demand for light for crops, the use of this type of ground film may have obvious limitations. Summary of the invention
[0006] The purpose of the present invention is to provide a fully biomass transparent liquid mulch film with photothermal conversion function and a preparation method thereof, which has efficient photothermal conversion capability, ensures the environmental friendliness of the material, significantly reduces dependence on petrochemical raw materials, and provides a more environmentally friendly and sustainable solution for agricultural production in high-altitude areas.
[0007] In order to achieve the above-mentioned purpose, the present invention provides a full-biomass transparent liquid mulch with photothermal conversion performance, which comprises the following components by weight: 2 to 4 parts of lignin-containing nanocellulose, 1 to 2 parts of biomass cross-linking agent, 25 to 30 parts of biomass plasticizer, and 65 to 70 parts of gelatin; wherein the lignin-containing nanocellulose is a nanocellulose with residual lignin obtained by finely treating the cellulose component in agricultural and forestry waste, and the finely treating is to pre-treat the agricultural and forestry waste with a low eutectic solvent and then perform mechanical grinding.
[0008] Preferably, the above-mentioned agricultural and forestry waste can be selected from any one of corn straw, wheat straw and bamboo.
[0009] Preferably, the biomass cross-linking agent can be selected from any one of tannic acid, laccase or gallic acid.
[0010] Preferably, the biomass plasticizer is selected from any one of glycerol, sorbitol or epoxidized soybean oil.
[0011] The liquid mulch provided by the present invention comprises lignin-containing nanocellulose prepared by the following method: mixing agricultural and forestry waste with a low eutectic solvent and reacting the mixture at 120 to 140° C. for 3 to 4 hours, performing solid-liquid separation after the reaction is completed, and mechanically grinding the solid matrix to obtain lignin-containing nanocellulose; the aspect ratio of the lignin-containing nanocellulose is greater than 200, the lignin content is higher than 17%, and the lignin phenolic hydroxyl content is increased by more than 30%.
[0012] Preferably, the above-mentioned low eutectic solvent is prepared by mixing betaine / lactic acid in a molar ratio of 1:2 and heating until the liquid becomes transparent; wherein the mass ratio of agricultural and forestry waste to the low eutectic solvent is preferably 1:(20-30).
[0013] The present invention also provides a method for preparing a fully biomass transparent liquid mulch film having a photothermal conversion function, comprising the following steps:
[0014] Step 1: adding the prepared lignin-containing nanocellulose, biomass plasticizer and gelatin into water in a certain weight ratio, and stirring and mixing at 50-60° C. to obtain a mixed solution;
[0015] Step 2: Add the biomass cross-linking agent to the mixed solution obtained in step 1, cross-link for 10 minutes at 50-60° C., and obtain a liquid mulch film after eliminating bubbles.
[0016] Preferably, the components in the above-mentioned liquid mulch are prepared according to the following weight parts, including 2-4 parts of lignin-containing nanocellulose, 1-2 parts of biomass cross-linking agent, 25-30 parts of biomass plasticizer, and 65-70 parts of gelatin; wherein the mass fraction of gelatin in the mixed solution is 5%.
[0017] The present invention also provides a more optimal method for preparing a liquid mulch film, wherein the ratio of the components is as follows: the mass fractions of gelatin and biomass plasticizer in the mixed solution are 5% and 2% respectively, the biomass cross-linking agent is 3% of the mass of gelatin, and the lignin-containing nanocellulose is 5% of the mass of gelatin.
[0018] The liquid mulch provided by the present invention can be used in the field of agricultural production to improve the photothermal conversion performance of the mulch, reduce the water vapor permeability of the mulch, reduce the damage of strong ultraviolet rays to crops, improve the photothermal conversion efficiency of the mulch, and improve agricultural production efficiency.
[0019] The present invention has the following advantages:
[0020] The present invention uses raw materials completely from renewable biomass resources, including agricultural and forestry wastes (such as corn straw, wheat straw and bamboo), biomass cross-linking agents (tannic acid, laccase and gallic acid), biomass plasticizers (glycerol, sorbitol and epoxidized soybean oil) and gelatin. This not only reduces the pollution of agricultural waste to the environment, but also conforms to the concept of green circular economy, and has the significant advantages of environmental protection, non-toxicity and sustainability. In addition, the use of all biomass effectively reduces the dependence on petrochemical-based synthetic materials, further promoting the development of agricultural production in a green and sustainable direction.
[0021] Lignin-containing nanocellulose (LCNFs) prepared by a green acidic low eutectic solvent (DES) pretreatment method exhibited a highly dispersed nanofiber structure with an aspect ratio greater than 200, indicating that it has excellent morphological characteristics. In addition, the lignin content in LCNFs exceeded 17%, and through this pretreatment method, the lignin underwent physical reorganization and chemical deconstruction, and its phenolic hydroxyl content increased by more than 30%. While the acidic DES graded the structure of the wood fibers, it can effectively protect the structure of cellulose and avoid its excessive loss during the treatment process. Thanks to the excellent aspect ratio and dispersion characteristics of LCNFs, the barrier properties of liquid mulch can be effectively improved.
[0022] In LCNFs, there are a large number of aromatic rings and conjugated functional groups in the molecular structure of lignin, which enables the lignin molecules to form a strong conjugated structure and exhibit unique optical properties through π-π intermolecular interactions. Specifically, the aromatic rings and conjugated functional groups of lignin not only give it UV absorption ability, but also provide the potential for sustainable photothermal conversion. In addition, the increase in the phenolic hydroxyl content in lignin helps to reduce the steric hindrance between molecules, thereby enhancing the interaction between molecules. This change not only optimizes the aggregated structure between molecules, but also promotes π-π stacking between conjugated molecules, thereby significantly improving the photothermal conversion efficiency. Therefore, in high-altitude areas, these characteristics of lignin in liquid mulch enable it to effectively convert ultraviolet light into heat energy, thereby increasing soil temperature and improving the growth environment of crops, while effectively preventing ultraviolet damage to crops. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Transmission electron microscopy images of LCNFs prepared in Invention Examples 1-5.
[0024] Figure 2 The UV-visible light transmittance spectra of the liquid mulch films prepared in Examples 1-5 of the invention. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Note: The experimental methods in the following examples are conventional methods unless otherwise specified, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples are all commercially available unless otherwise specified.
[0027] Example 1
[0028] This embodiment provides a method for preparing a liquid ground film, which is as follows:
[0029] (1) Preparation of lignin-containing nanocellulose (LCNFs)
[0030] Betaine / lactic acid were mixed in a molar ratio of 1:2 and heated to a liquid transparent green acidic low eutectic solvent (DES). 50g corn straw and DES were selected and added to a round-bottom flask in a mass ratio of 1:20, and continuously stirred and heated at 130°C for 3h. After the reaction, the mixture was cooled to about 80°C, and then 50mL of ethanol / water mixture (v / v=1:1) was added to reduce its viscosity, and the solid and liquid were separated by filtration to remove the residual DES and lignin in the cellulose solid component, and then the cellulose solid component was washed with hot water until the pH was neutral. The cellulose-rich matrix was prepared into a suspension with a concentration of 5‰, and after preliminary dispersion at 10000rpm for 30min in a homogenizer, it was poured into a sand mill for further crushing. When the position of the sand mill vernier caliper was 0, -1, -5 and -10, the distance between the two grinding discs was 200, 100, 50 and 10μm, and each parameter was executed ten times to prepare LCNFs.
[0031] In addition to corn straw as a cellulose donor, other agricultural and forestry wastes such as wheat straw or bamboo can also be selected.
[0032] (2) Preparation of liquid mulch
[0033] Gelatin and glycerol were prepared into a mixed solution at 5% and 2% respectively, and then LCNFs prepared in step (1) were added to the mixed solution at 5% of the mass of gelatin, and mixed evenly at 60°C, and then 3% of tannic acid was added at the mass of gelatin. After a cross-linking reaction was carried out at 60°C for 10 minutes, the liquid mulch was filtered and ultrasonically eliminated to obtain a liquid mulch. In order to facilitate subsequent testing, the prepared liquid mulch was poured into a special template, placed horizontally, and dried at room temperature to form a film. The thickness of the obtained mulch was about 0.1 mm.
[0034] The tannic acid used as the biomass cross-linking agent can be replaced by laccase or gallic acid; the glycerol used as the biomass plasticizer can be replaced by sorbitol or epoxidized soybean oil.
[0035] Example 2
[0036] This embodiment also provides a method for preparing a liquid mulch film, which differs from the embodiment 1 in that: the DES in step (1) of the embodiment 1 is replaced with betaine / lactic acid in a molar ratio of 1:2 to prepare a solution, and p-toluenesulfonic acid is added based on 3% of the total mass of DES, and heated until the liquid is transparent to synthesize DES. The other steps are the same as those of the embodiment 1.
[0037] Example 3
[0038] This embodiment also provides a method for preparing a liquid mulch film, which is different from the embodiment 1 in that the DES in step (1) of the embodiment 1 is replaced with betaine / lactic acid in a molar ratio of 1:2 to prepare a solution, and ferric chloride is added based on 3% of the total mass of DES, and heated until the liquid is transparent to synthesize DES. The other steps are the same as those of the embodiment 1.
[0039] Example 4
[0040] This embodiment also provides a method for preparing a liquid mulch film, which differs from the embodiment 1 in that: the DES in step (1) of the embodiment 1 is replaced with betaine / lactic acid in a molar ratio of 1:2 to prepare a solution, and citric acid is added based on 3% of the total mass of the DES, and heated until the liquid is transparent to synthesize the DES. The other steps are the same as those of the embodiment 1.
[0041] Example 5
[0042] This embodiment also provides a method for preparing a liquid mulch film, which differs from the embodiment 1 in that: the DES in step (1) of the embodiment 1 is replaced with betaine / lactic acid in a molar ratio of 1:2 to prepare a solution, 3% of phosphoric acid based on the total weight of DES is added, and the solution is heated until the liquid is transparent to synthesize DES. The other steps are the same as those of the embodiment 1.
[0043] Experimental Example 1 Analysis of straw components before and after DES pretreatment
[0044] In this experimental example, the composition changes of straw cellulose, lignin and hemicellulose before and after DES pretreatment in Examples 1-5 were tested and analyzed using the Klason method (TAPPI standard method T-222). Specific parameters are shown in Table 1 below.
[0045] Table 1 Changes in the composition of cellulose, lignin and hemicellulose in straw before and after DES pretreatment
[0046]
[0047] As can be seen from Table 1, after the five groups of different DES pretreatments in Examples 1-5, the compact structure of wood cellulose is opened, the cellulose in the solid component is purified to varying degrees, the hemicellulose content is significantly reduced, and the lignin content remains stable, and the lignin content is higher than 17%. This stable lignin component and the fully swollen cellulose component lay a good foundation for the subsequent preparation of lignin-containing nanofibers (LCNFs), and can enhance the micro-nano exfoliation effect of cellulose.
[0048] Experimental Example 2 Evaluation of the degree of micro-nano exfoliation of LCNFs
[0049] For the LCNFs prepared in Examples 1-5 of the present invention, the aspect ratios were estimated by sedimentation experiments of LCNFs with different mass concentrations to preliminarily evaluate the micronization degree of cellulose. The specific steps are as follows:
[0050] 15 mL of LCNFs were prepared with concentrations of 0.5, 1.0, 1.5, and 2.0 kg / m 3 The suspension was then transferred to a 15 mL centrifuge tube, stirred and sonicated to completely suspend the LCNFs in the solution. The centrifuge tube was then inverted to allow the LCNFs to settle for 48 hours, and the height of the sediment in the centrifuge tube was measured.
[0051] Then the following quadratic equation is used to fit the relationship between LCNFs concentration and sediment height. The specific formula is as follows:
[0052] y=ax 2 +bx
[0053] Among them, x is the ratio of the sediment height to the total liquid level, y is the LCNFs concentration, and the linear coefficient b is the gel point concentration (obtained by substituting the x and y data into the above quadratic equation fitting. When processing the data, a scatter plot of x and y is drawn, and then the nonlinear curve fitting of origin is used to obtain a curve that fits the scatter plot. The values of a and b are automatically displayed according to the fitted curve equation).
[0054] Finally, the aspect ratio is calculated using the following formula:
[0055]
[0056] Where A is the aspect ratio, ρ is the density of LCNF (1500 kg / m 3 ). The specific data are shown in Table 2 below.
[0057] Table 2 Aspect ratio of products obtained from different embodiments
[0058]
[0059] As can be seen from Table 2 above, the LCNFs prepared by the five groups of embodiments of the present invention all have a high aspect ratio, and all are greater than 200, indicating that the cellulose micro-nano exfoliation effect is excellent, because the DES pretreatment can effectively destroy the compact structure of lignocellulose, and its swelling effect makes the cellulose chain easier to unfold and separate. The aspect ratio data shows a negative correlation trend with the lignin content in LCNFs, because lignin can form a tight three-dimensional network with cellulose and hemicellulose through ether bonds and carbon-carbon bonds, enhance the adhesion between each molecular chain, and weaken the nano-exfoliation of cellulose, which ultimately leads to the aspect ratio of LCNFs with high lignin content being slightly lower than that of LCNFs with low lignin content. LCNFs with a high aspect ratio can form a denser three-dimensional cross-linked network in the process of preparing liquid mulch, increase the diffusion path of gas and water vapor through the mulch, and thus improve the barrier performance of the film.
[0060] Experimental Example 3 Transmission electron microscopy observation of LCNFs
[0061] The LCNFs prepared in Examples 1-5 were scanned by transmission electron microscopy (TEM), and the results were as follows: Figure 1 As shown, it can be seen that Examples 1-5 successfully prepared LCNFs, and their microscopic morphology shows that LCNFs are long whisker-like structures composed of single cellulose fibers with a high degree of exfoliation and some lignin fragments. This structure has highly dispersed nanostructured features and a high aspect ratio, and the high dispersibility of this structure provides a good basis for its application in liquid mulch.
[0062] Experimental Example 4 Determination of lignin phenolic hydroxyl content in LCNFs
[0063] The content of phenolic hydroxyl functional groups of lignin in the LCNFs prepared in Examples 1-5 was quantitatively analyzed by phosphorus spectrum nuclear magnetic resonance, with the original lignin as a control. The specific data are shown in Table 3 below.
[0064] Table 3 Determination of lignin phenolic hydroxyl functional group content in LCNFs
[0065]
[0066] As can be seen from Table 3, the phenolic hydroxyl content of lignin in the LCNFs prepared in the five groups of embodiments has been improved to varying degrees compared with the original straw lignin. This phenomenon is due to the partial degradation of lignin during the DES treatment, which leads to the breakage of the lignin molecular chain, thereby releasing the phenolic hydroxyl groups originally hidden in the complex lignin network structure. In addition, the cleavage of the β-O-4 bond of lignin during the DES treatment further increases the possibility of structural degradation, which also exposes more phenolic hydroxyl groups. The increase in the phenolic hydroxyl content helps lignin to play a more effective role in the photothermal conversion performance of liquid mulch, thereby improving its application effect in agriculture.
[0067] Experimental Example 5 Water Vapor Barrier Performance of Liquid Ground Film
[0068] The water vapor permeability (WVT) test method of the liquid mulch prepared in Examples 1-5 refers to the "Determination of Water Vapor Permeability of Plastic Films and Sheets-Cup Weight Gain and Weight Loss Method (GB / T 1037-2021)", and gelatin film is used as a control. The specific data are shown in Table 4 below.
[0069] Table 4 Water Vapor Transmission Rate (WVT) Test Results of Liquid Ground Film
[0070]
[0071] The water vapor permeability of the liquid mulch containing LCNFs and the pure gelatin film without LCNFs prepared in five examples was measured. The water vapor permeability of the liquid mulch obtained by the test was much better than the Class A standard of 800g / (m 2 ·24h). It can be seen that LCNFs significantly improve the water vapor barrier properties of liquid mulch. This effect is mainly attributed to the high aspect ratio and good dispersibility of LCNFs. When LCNFs are added to liquid mulch, their hydroxyl groups can form chemical crosslinks with the amino and hydroxyl groups in the gelatin matrix to form a dense three-dimensional crosslinked network, which prolongs the path of water vapor through the membrane and thus reduces the water vapor permeation.
[0072] Experimental Example 6 Optical transparency test of liquid ground film
[0073] The liquid mulch prepared in Examples 1-5 was tested by UV-visible light transmittance spectrum. Figure 2 As shown by Figure 2It can be seen that the liquid mulch prepared in Examples 1-5 has almost 100% shielding effect on the B band (280-320nm) and C band (200-280nm) of ultraviolet light, and can effectively protect crops from ultraviolet damage. This feature is particularly suitable for high-altitude areas to prevent strong ultraviolet damage to crops. At the same time, the liquid mulch has excellent optical transparency, ensuring visible light transmission, thereby promoting plant photosynthesis and improving agricultural production efficiency. The combination of these two properties effectively optimizes the growth environment of high-altitude crops.
[0074] Experimental Example 7: Testing of the photothermal conversion performance of liquid mulch film
[0075] The photothermal conversion performance of the liquid mulch prepared in Examples 1-5 was tested by using a conventional agricultural sprayer to evenly spray the liquid mulch on the leveled soil surface, and then regularly testing the soil surface temperature under simulated xenon lamp simulated sunlight conditions, using gelatin film as a control. The specific data are shown in Table 5 below.
[0076] Table 5 Photothermal conversion performance test of liquid mulch
[0077]
[0078] Table 5 shows the temperature rise of the soil under simulated light conditions by testing five groups of examples of liquid mulch with LCNFs added and pure gelatin liquid mulch. It can be seen that the liquid mulch with LCNFs added has a faster temperature increase rate, indicating that it has excellent photothermal conversion performance. This is mainly because there are a large number of aromatic rings and conjugated functional groups in the molecular structure of lignin, which enables the lignin molecules to form a strong conjugated structure and exhibit excellent photothermal conversion performance through π-π intermolecular interactions. In addition, the increase in the phenolic hydroxyl content in lignin helps to reduce the steric hindrance between molecules, thereby enhancing the interaction force between molecules. This change not only optimizes the aggregated structure between molecules, but also promotes π-π stacking between conjugated molecules, thereby significantly improving the photothermal conversion efficiency of the liquid mulch. These advantages make the photothermal conversion performance have important application value in agriculture and ecosystems in high-altitude areas.
[0079] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A fully biomass transparent liquid mulch film with photothermal conversion performance, characterized in that: The components include the following in parts by weight: 2-4 parts of lignin nanocellulose, 1-2 parts of biomass cross-linking agent, 25-30 parts of biomass plasticizer, and 65-70 parts of gelatin; The lignin-containing nanocellulose is a nanocellulose with residual lignin obtained by finely treating the cellulose components in agricultural and forestry wastes, wherein the finely treating the agricultural and forestry wastes is performed by pre-treating the agricultural and forestry wastes with a low eutectic solvent and then mechanically grinding the pre-treated cellulose components.
2. The liquid ground film according to claim 1, characterized in that: The agricultural and forestry waste is selected from any one of corn straw, wheat straw and bamboo.
3. The liquid ground film according to claim 1, characterized in that: The biomass cross-linking agent is selected from any one of tannic acid, laccase or gallic acid.
4. The liquid ground film according to claim 1, characterized in that: The biomass plasticizer is selected from any one of glycerol, sorbitol or epoxidized soybean oil.
5. The liquid ground film according to claim 1, characterized in that: The lignin-containing nanocellulose is prepared by the following method: The agricultural and forestry waste is mixed with a low eutectic solvent and reacted at 120-140° C. for 3-4 hours. After the reaction is completed, solid-liquid separation is performed, and the solid matrix is mechanically sand-milled to obtain the lignin-containing nanocellulose; the aspect ratio of the lignin-containing nanocellulose is greater than 200, and the lignin content is higher than 17%.
6. The liquid ground film according to claim 5, characterized in that: The low eutectic solvent is prepared by mixing betaine / lactic acid in a molar ratio of 1:2 and heating until a liquid becomes transparent; the mass ratio of the agricultural and forestry waste to the low eutectic solvent is 1:(20-30).
7. The method for preparing a liquid ground film according to any one of claims 5 to 6, characterized in that: The steps include: Step 1: adding the prepared lignin-containing nanocellulose, biomass plasticizer and gelatin into water in a certain weight ratio, and stirring and mixing at 50-60° C. to obtain a mixed solution; Step 2: adding the biomass cross-linking agent to the mixed solution obtained in step 1, cross-linking for 10 minutes at 50-60° C., and obtaining the liquid mulch film after eliminating bubbles.
8. The preparation method according to claim 7, characterized in that: The components in the liquid mulch film are prepared according to the following weight parts, including 2-4 parts of lignin-containing nanocellulose, 1-2 parts of biomass cross-linking agent, 25-30 parts of biomass plasticizer, and 65-70 parts of gelatin; the mass fraction of the gelatin in the mixed solution is 5%.
9. The preparation method according to claim 8, characterized in that: The proportions of the components are as follows: the mass fractions of the gelatin and the biomass plasticizer in the mixed solution are 5% and 2% respectively, the biomass cross-linking agent is 3% of the mass of the gelatin, and the lignin-containing nanocellulose is 5% of the mass of the gelatin.
10. The use of the liquid mulch film according to any one of claims 1 to 6 in the field of agricultural production, characterized in that: The application includes improving the light-to-heat conversion performance of the mulch film, reducing the water vapor permeability of the mulch film, reducing the damage of strong ultraviolet rays to crops, improving the light-to-heat conversion efficiency of the mulch film, and improving agricultural production efficiency.
Citation Information
Patent Citations
Biodegradable temperature-increasing mulching film and preparation method thereof
CN117048163A
Preparation method of biodegradable weeding and warming mulching film
CN117946507A